Evaluation of 230 patients with relapsed/refractory deletion 17p chronic lymphocytic leukaemia treated with ibrutinib from 3 clinical trials. (5th June 2018) - Jones, Jeffrey; Mato, Anthony; Coutre, Steven; Byrd, John C.; Furman, Richard R.; Hillmen, Peter; Osterborg, Anders; Tam, Constantine; Stilgenbauer, Stephan; Wierda, William G.; Heerema, Nyla A.; Eckert, Karl; et al.
Summary: Patients with chronic lymphocytic leukaemia/small lymphocytic lymphoma (CLL/SLL) with deletion 17p [del(17p)] have poor outcomes with chemoimmunotherapy. Ibrutinib is indicated for the treatment of CLL/SLL, including del(17p) CLL/SLL, and allows for treatment without chemotherapy. This integrated analysis was performed to evaluate outcomes in 230 patients with relapsed/refractory del(17p) CLL/SLL from three ibrutinib studies. With a median of 2 prior therapies (range, 1–12), 18% and 79% of evaluable patients had del(11q) or unmutated IGHV, respectively. With a median follow‐up of 28 months, overall response rate was 85% and estimated 30‐month progression‐free and overall survival rates were 57% [95% confidence interval (CI) 50–64] and 69% (95% CI 61–75), respectively. Patients with normal lactate dehydrogenase or no bulky disease had the most favourable survival outcomes. Sustained haematological improvements in haemoglobin, platelet count and absolute neutrophil count occurred in 61%, 67% and 70% of patients with baseline cytopenias, respectively. New onset severe cytopenias and infections decreased in frequency over time. Progression‐free and overall survival with ibrutinib surpass those of other therapies for patients with del(17p) CLL/SLL. These results provide further evidence of the robust clinical activity of ibrutinib in difficult‐to‐treat CLL/SLL populations.